Analisis bibliometrik tentang tren penerapan kebijakan kota hijau (green city) - Vilosa, Bias; Yuadi, Imam (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
Environmental pollution continues to occur due to the times, so it is necessary to make improvements through sustainable development that is environmentally friendly. One form of support for sustainable development can be realized in the implementation of green city policies. To find out more about the implementation of green city policies, it can be done through analyzing trends in the application of green city policies from 2013 - 2023 in literature review research that has been published in the Web of Science (WoS) and Scopus databases using bibliometric analysis. From the search for scientific articles on green city policies, the data was visualized with the VOSviewer and RStudio applications using the biblioshiny method. The results of the research analysis are; the scope of the most popular topics with 6 (six) green city discussions, topic trends namely urban planning, sustainability, and green city policy, the high average number of citations in 2015 due to world commitment and the green city phenomenon, and the most countries that publish the USA, China, and the UK. Research trends in the implementation of green city policies produce positive data and collaborate with each other.